Nietypowość romskiego ucznia i jego możliwości rozwoju kreatywności - Novotná, Jarmila (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2013)
This study discusses issues related to the education of Romani children and their development in contemporary schools. The focus is on the options for developing Romani children’s creativity and skills. The author provides a theoretical analysis of the uniqueness of Romani children; in particular, she analyzes their specific psychological functioning. The author describes a creativity development program which has been designed for Romani pupils to foster their uniqueness. This program has been experimentally verified. The study focuses on the theoretical basis, objectives, methodology and results of an experiment which was aimed to test the effectiveness of the creativity development program in educating Romani children. Changes in Romani children’s creativity are subjected to quantitative and qualitative analysis. The interpretation of research results and findings provides innovative solutions for teaching Romani childre.